Stephen’s Ministry Concept as a Transformative Deacon Prototype Model Based on Acts 6:5 In Pontianak City - Syahdin, Syahdin; Purwoko, Paul Sentot; Wahyuni, Sri; Sukarna, Timotius (Technium Social Sciences Journal, 2023)
The Bible in Acts 6 records that Stephen was the prototype of the first deacon in the early history of God’s church ministry on this earth. The researcher will describe Stephen as a transformative deacon prototype based on Acts 6:1-7:9-10 among the seven deacons in the early congregation who were chosen by the congregation to carry out the tasks of diaconal (social) service in the early congregation. . This study aims to analyze the concept of Stephen’s ministry as a transformative deacon prototype model based on Acts 6:1-7:9-10. The research method used is qualitative implementation of the concept of Stephen’s ministry, a transformative deacon prototype model based on Acts 6:1-7:910 as principles and formulas. The results of the research state that the prototype model of transformative deacon applied is charismatic, reformative and transformative diaconia. Therefore, steps must be rethought to make the relevance of reformative and transformative diaconal services in the form of a touch in all fields as a whole and cross-sectoral which causes the transformation of life. This transformation primarily brings souls to enter the Kingdom of God as mandated by the Lord Jesus Christ in Matthew 28:18-20. steps must be rethought to make the relevance of reformative and transformative diaconal services in the form of a touch in all fields as a whole and cross-sectoral which causes the transformation of life. This transformation primarily brings souls to enter the Kingdom of God as mandated by the Lord Jesus Christ in Matthew 28:18-20. steps must be rethought to make the relevance of reformative and transformative diaconal services in the form of a touch in all fields as a whole and cross-sectoral which causes the transformation of life. This transformation primarily brings souls to enter the Kingdom of God as mandated by the Lord Jesus Christ in Matthew 28:18-20.